Teaching finance in period of uncertainity - Mayall, Peter (University of the Fraser Valley, 2011)
Universities strive to tailor relevance of the courses they teach to the real worldand the application of their material to the current financial environment. Theproblem facing teachers is the evergreen rules that they are used to applying arebeing overridden by the volatility of the marketplace and the velocity of thechanges. Technology is speeding up the circulation of knowledge to the point thatresponses to marketplace events are being distorted by sudden volumes of tradesthat it was not designed to handle in an orderly fashion. The challenge is to usethe edge that technology provides to change teaching methods and account forthese sudden financial events that do so much to distort the orderly marketplacethat previously responded to commonly used financial models. This study looks atthe tools that technology provides and poses the question as to whether this willbe enough going forward to equip students with the knowledge to handle thevolatility issues in the marketplace and their careers in finance.